Intolerance to Early Nasogastric and Nasojejunal Enteral Nutrition in Patients with Moderately Severe Acute Pancreatitis - A. O. Sivkov; O. G. Sivkov; I. N. Leiderman; E. Yu. Zaitsev; I. B. Popov (Неотложная медицинская помощь, 2022)
RELEVANCE Early enteral nutrition is an essential element of intensive care for acute pancreatitis. Its intolerance is manifested by high gastric residual volumes, pain syndrome, bloating, diarrhea, nausea and vomiting. The relevance of our study is determined by the lack of information on how the routes of nutrient delivery affect its tolerability considering the gradual «asperprotocol» increase in nutrition volumes for patients with moderately severe acute pancreatitis.THE AIM OF THE STUDY Was to identify the key factors that determine intolerance to early nasogastric and nasojejunal enteral feeding in ICU patients with the early phase of moderately severe acute pancreatitis.MATERIAL AND METHODS We conducted an open randomized controlled trial. Out of 64 patients with predicted severe course of acute pancreatitis, we identified a cohort with moderately severe acute pancreatitis, in which 17 (51.5%) patients received early enteral nutrition through a nasogastric tube, and 16 (48.5%) via an endoscopically placed nasojejunal tube. The criteria for nutrition intolerance were as follows: nasogastric tube discharge of more than 500±100 ml at a time or more than 500 ml/day in comparison with the enterally administered during this period, increased pain, bloating, diarrhea, nausea and vomiting. Using the method of logistic regression, indicators with prognostic significance were determined. The null hypothesis was rejected at p<0.05.RESULTS Regardless of the nutrition route, the progression of multiple organ failure increases the incidence of high gastric residual volumes (SOFA — OR (odds ratio) — 1.337, 95% CI (confidence interval) 1.001–1.787; p = 0.049). Pain syndrome is less common on the day of surgery (OR 0.258, 95% CI 0.110–0.606; p=0.002). Nasojejunal feeding was associated with a lower incidence of nausea and vomiting (OR 0.168, 95% CI 0.06–0.473; p=0.001), but with more diarrhea (OR 6.411, 95% CI 1.274–32.262; p=0.024).CONCLUSION The progression of multiple organ failure increases the incidence of high gastric residual volumes. The pain syndrome is less pronounced on the day of surgery and more intense in case of nasogastric nutrition. Postpyloric nutrition reduces the incidence of nausea and vomiting, but increases diarrhea.